2019
DOI: 10.1002/aic.16592
|View full text |Cite
|
Sign up to set email alerts
|

Optimal rate allocation for production and injection wells in an oil and gas field for enhanced profitability

Abstract: An oil and gas field requires careful operational planning and management via production optimisation for increased recovery and long-term project profitability. This paper addresses the challenge of production optimisation in a field undergoing secondary recovery by water flooding. The field operates with limited processing capacity at the surface separators, pipeline pressure constraints and water injection constraints; an economic indicator (Net Present Value -NPV) is used as the objective function. The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…It is observed that within the first 5 iterations, the algorithm is able to find a near optimal solution; the solution of CS2-IP is obtained with fewer number of iterations. Compared to a methodology that requires numerous direct calls to a high-fidelity simulator or an approximation of the simulator's output (as shown in Epelle and Gerogiorgis, 2019c), the herein implemented algorithm attains optimality in fewer iterations. All computations were performed on an Intel Core i7-6700 CPU @ 3.40GHz machine with 4 processing cores.…”
Section: Computational Performance Of Cs1 and Cs2mentioning
confidence: 99%
“…It is observed that within the first 5 iterations, the algorithm is able to find a near optimal solution; the solution of CS2-IP is obtained with fewer number of iterations. Compared to a methodology that requires numerous direct calls to a high-fidelity simulator or an approximation of the simulator's output (as shown in Epelle and Gerogiorgis, 2019c), the herein implemented algorithm attains optimality in fewer iterations. All computations were performed on an Intel Core i7-6700 CPU @ 3.40GHz machine with 4 processing cores.…”
Section: Computational Performance Of Cs1 and Cs2mentioning
confidence: 99%
“…The complicated economics, technical operational challenges and the overall multifaceted nature of industrial drilling activities have made it open to multiscale modelling, robust simulation methodologies and state of the art experimentation techniques for accurate understanding of the flow scenarios and optimal parameters necessary for a problem-free operation. [8][9][10] Over the past decades, the field has attracted numerous successful contributions from the chemical, petroleum and mechanical engineering communities for well trajectory optimisation and particle removal/hole cleaning processes. More recently, a body of literature specifically belonging to the process systems engineering community has emerged; majorly targeting wellbore stability challenges with respect to the fracture pressure and pore pressure.…”
Section: Take Down Policymentioning
confidence: 99%
“…Aadnoy [23] established a collapse pressure model that considered both bedding occurrence and shale strength weakening, and analyzed the factors affecting the collapse pressure distribution. Combined with the weak plane strength criterion, Ma et al [24][25][26][27][28][29] established an analysis model for the wellbore stability of layered shale horizontal wells, and analyzed the effects of bedding occurrence and water content on the collapse pressure of horizontal wells. However, the current research on shale wellbore stability in China mainly focuses on the marine shale of Longmaxi Formation in Sichuan, and the wellbore instability of continental shale in the north of Songliao Basin has not been studied.…”
Section: Introductionmentioning
confidence: 99%